Discovery of novel plant peptides as strong inhibitors of metalloprotein-ases - Carrilho, D.M.; Duarte de Almeida, I.; Ricardo, C.P.P.; Duque-Magalhães, M.C. (Protein and Peptide Letters, 2009)
Five novel metalloproteinase protein inhibitors (MPIs) with molecular mass between 5.6 and 8.9 kDa and acid/neutral pI were detected in lupin seeds and exhibited strong inhibitory activities against thermolysin and/or gelatinase B. These novel peptides constitute not only the first MPIs described in plants but also the first plant peptides with inhibitory activity against a matrixin.